Female directors and real activities manipulation: Evidence from China - Jin-hui Luo; Yuangao Xiang; Zeyue Huang (China Journal of Accounting Research, 2017)
Unlike previous studies that focus on accrual-based earnings management, this study analyzes real activities manipulation and investigates whether female directors on boards of directors (BoDs) affect managers' real activities manipulation. Using a large sample of 11,831 firm-year observations from Chinese listed companies from the 2000 to 2011 period, we find that higher female participation on BoDs is associated with lower levels of real activities manipulation, and that this negative relationship is stronger when female directors have higher ownership. These results hold for a battery of robustness checks. Overall, our findings indicate that board gender diversity may serve as a substitute mechanism for corporate governance to curb real activities manipulation and thus provide interested stakeholders with higher quality earnings reports.
Keywords: G32; G34; J70; M41; 650; Female director; Gender diversity; Earnings management; Real activities manipulation; Corporate governance